Lawyers for the poor : legal advice, voluntary action and citizenship in England, 1890-1990 - Bradley, Kate, Dr (Manchester scholarship online., 2020)
This text examines the development of legal advice services in England, from their origins in 'Poor Man's Lawyer' voluntary work in the 1890s, through the growth of mutual schemes and newspaper advice bureaux, and to the challenges of meeting the needs of socially-excluded groups in the post-war period.